2000
DOI: 10.1080/00223980009600849
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Locus of Control: Assessing More Than Meets the Eye?

Abstract: Ambiguities in the conceptions and measurement of locus of control were investigated in this study. Specifically, some psychometric properties of several widely used measures of perceived behavior-outcome contingency, interpersonal power, and social self-efficacy were assessed. To different degrees, the results indicated that all three measures of perceived behavior-outcome contingency lacked convergent and discriminant validity. Implications for interpreting past research, directions for future investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
1
23
0
2
Order By: Relevance
“…Out of all the characteristics extensively scrutinized, locus of control (LoC) is another trait. It is an identity variable that is identified with the summed up the desires of a man whether he has the capacity to control life situations (Leone and Burns, 2000). As stated by Rotter (1966) in terms of how many personal obligations they recognize and acknowledge for their conduct and outcomes.…”
Section: Locus Of Controlmentioning
confidence: 99%
“…Out of all the characteristics extensively scrutinized, locus of control (LoC) is another trait. It is an identity variable that is identified with the summed up the desires of a man whether he has the capacity to control life situations (Leone and Burns, 2000). As stated by Rotter (1966) in terms of how many personal obligations they recognize and acknowledge for their conduct and outcomes.…”
Section: Locus Of Controlmentioning
confidence: 99%
“…Reference [26] states that locus of control is an individual characteristics that measure the extent to which people believe they are responsible for the consequences of their behaviour, intentions and outcomes. Prior studies have shown that when internals accept a position with a firm they tend to have a higher commitment to the firm relative to externals.…”
Section: B Locus Of Control and Intention To Report Errorsmentioning
confidence: 99%
“…Intentions Internal Locus of control (LoC) is a personality variable that is related to the generalized expectations of a person on whether he/she will be able to control the events in life as an entrepreneur [20]. The LoC represents the degree to which individuals believe that their achievements are dependent on their own behaviour.…”
Section: Internal Locus Of Control and Self-employmentmentioning
confidence: 99%